Lateral ventilation performance for removal of pulsating buoyant jet under the influence of high-temperature plume. Issue 4 (April 2020) - Wang, Yi; Cao, Lei; Huang, Yanqiu; Cao, Yingxue
Lateral exhaust systems have commonly been applied to capture polluted buoyant jets in many industrial processes, such as casting and metallurgy. Compared with the normal conditions of design manuals, the capture efficiency of a lateral exhaust hood (LEH) is often weakened by two factors in actual processes: the unsteady buoyant jet released from the operating surface, and the plume formed above a high-temperature workpiece placed between the LEH and the operating surface. In this study, through experiments and numerical simulations, a pulsatile phenomenon was found in the velocity and concentration distribution of the unsteady buoyant jet. Results show that the contaminate escape ratio is pulsatile; it rises with the instantaneous increase in the buoyant jet velocity and gradually decreases to a constant value. This study not only reveals the air distribution of pulsating buoyant jet but also analyses the effect of the pulsating buoyant jet and high-temperature plume on lateral ventilation system capture efficiency and provides a possible guidance for future design of new building ventilation technologies.